The In vitro Effects of Nano-encapsulated Conjugated Linoleic Acid on Stability of Conjugated Linoleic Acid and Fermentation Profiles in the Rumen - Heo, Wan; Kim, Eun Tae; Cho, Sung Do; Kim, Jun Ho; Kwon, Seong Min; Jeong, Ha Yeon; Ki, Kwang Seok; Yoon, Ho Baek; Ahn, Young Dae; Lee, Sung Sill; Kim, Young Jun (Animal bioscience, 2016)
This study was aimed to evaluate the stability of conjugated linoleic acids (CLAs) by nano-encapsulation against in vitro ruminal biohydrogenation by microbial enzymatic conversion. CLAs (free fatty acid form of CLA [CLA-FFA], nano-encapsulated CLA-FFA, triglyceride form of CLA [CLA-TG], and nano-encapsulated CLA-TG) were used in the in vitro fermentation experiments. When Butyrivibrio fibrisolvens (B. fibrisolvens) was incubated with CLA-FFAs, the concentrations of cis-9, trans-11 CLA and vaccenic acid (VA) slightly was decreased and increased by nano-encapsulation, respectively. When B. fibrisolvens was incubated with CLA-TG, the concentrations of cis-9, trans-11 CLA and VA decreased, but these were increased when B. fibrisolvens was incubated with nano-encapsulated CLA-TG. The nano-encapsulation was more effective against the in vitro biohydrogenation activity of B.fibrisolvens incubated with CLA-FFA than with CLA-TG. In the in vitro ruminal incubation test, the total gas production and concentration of total volatile fatty acids incubated with nano-encapsulated CLA-FFA and CLA-TG were increased significantly after 24 h incubation (p<0.05). Nano-encapsulated CLA-FFA might, thus, improve the ruminal fermentation characteristics without adverse effects on the incubation process. In addition, nano-encapsulated CLA-FFA increased the population of Fibrobacter succinogenes and decreased the population of B. fibrisolvens population. These results indicate that nano-encapsulation could be applied to enhance CLA levels in ruminants by increasing the stability of CLA without causing adverse effects on ruminal fermentation.